2008
DOI: 10.4049/jimmunol.181.8.5775
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis Associates with a Type 1 IFN Signature in Peripheral Blood Neutrophils

Abstract: Peripheral blood neutrophils from periodontitis patients exhibit a hyperreactive and hyperactive phenotype (collectively termed hyperresponsivity) in terms of production of reactive oxygen species (ROS). The molecular basis for this phenomenon, however, has yet to be determined. Our objectives were to identify genes differentially expressed in hyperresponsive peripheral blood neutrophils from chronic periodontitis patients relative to periodontally healthy controls and use these data to identify potential cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 73 publications
4
78
0
Order By: Relevance
“…A similar pattern of neutrophil migration has been described in COPD where cells displayed poor migratory accuracy but with random movement in all directions at increased speed 72. Recent publications have also described compromised neutrophil bacterial phagocytosis in periodontitis86 (studies in COPD are less clear); enhanced neutrophil-derived ROS87,88 and increased NET formation in both COPD and periodontitis,89,90 all of which could contribute to the sustained inflammation that characterizes both the conditions 34,53. The cause for such injurious cell behavior is unclear, and it is unknown whether neutrophil dysfunction precedes or is a consequence of disease.…”
Section: Mechanismsmentioning
confidence: 56%
“…A similar pattern of neutrophil migration has been described in COPD where cells displayed poor migratory accuracy but with random movement in all directions at increased speed 72. Recent publications have also described compromised neutrophil bacterial phagocytosis in periodontitis86 (studies in COPD are less clear); enhanced neutrophil-derived ROS87,88 and increased NET formation in both COPD and periodontitis,89,90 all of which could contribute to the sustained inflammation that characterizes both the conditions 34,53. The cause for such injurious cell behavior is unclear, and it is unknown whether neutrophil dysfunction precedes or is a consequence of disease.…”
Section: Mechanismsmentioning
confidence: 56%
“…In a preliminary set of patients (n = 31) we identified the ISGs that account for the greatest variability in expression. These genes ( MX1 , ISG15 , IFIT1 , and IFIT3 ) are prototypical ISGs, previously shown to be highly expressed in stimulated neutrophils [66,68,69], lymphocytes [37], peripheral blood mononuclear cells [38,39], and whole blood [70]. Using a panel of three of these unrelated genes in a non-overlapping cohort (n = 120), we found that ARDS patients with ISG expression greater or less than one standard deviation from the mean had significantly worse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Post-treatment, DNA release was determined as above. No TNF-α priming was employed in this study, as peripheral blood neutrophils from periodontitis patients are already primed within the circulation by plasma cytokines (Wright et al ., 2008; Dias et al ., 2010). …”
Section: Methodsmentioning
confidence: 99%